2004
DOI: 10.1207/s15516709cog2806_6
|View full text |Cite
|
Sign up to set email alerts
|

The use of recognition in group decision‐making

Abstract: Goldstein and Gigerenzer (2002) [Models of ecological rationality: The recognition heuristic. Psychological Review, 109 (1), [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] found evidence for the use of the recognition heuristic. For example, if an individual recognizes only one of two cities, they tend to infer that the recognized city has a larger population. A prediction that follows is that of the less-is-more effect: Recognizing fewer cities leads, under certain conditions, to more accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Our set of simple models demonstrate that both aggregated and expert rules can enable accurate collective solutions to challenging problems [9], as this has also been found in human group decision-making [27], [28]. Both choice rules we have considered do not necessarily require advanced cognitive abilities, but only that individuals have the potential to acquire information through social interaction, and respond positively to those who possess pertinent information [9], [12] (Models 1 and 2), or update their choice rules based on the success of the previous decisions [29] (Model 3).…”
Section: Resultssupporting
confidence: 55%
“…Our set of simple models demonstrate that both aggregated and expert rules can enable accurate collective solutions to challenging problems [9], as this has also been found in human group decision-making [27], [28]. Both choice rules we have considered do not necessarily require advanced cognitive abilities, but only that individuals have the potential to acquire information through social interaction, and respond positively to those who possess pertinent information [9], [12] (Models 1 and 2), or update their choice rules based on the success of the previous decisions [29] (Model 3).…”
Section: Resultssupporting
confidence: 55%
“…Several demonstrations have shown that having heard of a larger number of objects is sometimes associated with lower inferential accuracy, both for individual decision makers (e.g., Goldstein and Gigerenzer, 2002) and groups (Reimer and Katsikopoulos, 2004). However, reviewing 10 data sets where the recognition validity was larger than the knowledge validity – one of the conditions for the effect highlighted by Goldstein and Gigerenzer (2002) – Pachur (2010) concluded that the evidence for the effect is mixed.…”
Section: The Recognition Heuristic As a Descriptive Modelmentioning
confidence: 99%
“…We can use the majority rule (which simplifies computation by just tallying yes/ no judgments rather than, for instance, weighting them according to importance of different judges) and other heuristics to make group decisions about people as potential employees, based on the distribution of information within our group (Todd et al, in press). Patterns of recognition knowledge gained by individuals via social exchange can be successfully exploited by the recognition heuristic mentioned earlier (Gigerenzer et al, 1999) to decide which of two items is larger (e.g., cities) or more successful (e.g., tennis players or stocks), and such recognition patterns are also given prominence in group decision making (Reimer & Katsikopoulos, 2004). But people do not use the recognition heuristic blindly-rather they seem to evaluate intuitively its ecological rationality for a given situation (via mechanisms that have been associated with particular neural structures-see Gigerenzer, 2007).…”
Section: Relevant Structure In Environmentsmentioning
confidence: 99%